Effects of three-month paraquat exposures on the intestine and major organs of rats:a histopathological assessment - Taghdi, Manal Hussein Alhadi (2020)
Paraquat is an herbicide that was use worldwide due to the high cost-effectiveness and fast acting herbicidal activities. Nonetheless, the use of paraquat has also led to several health and environmental adverse consequences. Many chronic diseases such as Parkinson’s disease, dermatitis, impaired lung function, and cancer have been associated with paraquat exposure in epidemiological studies. Nonetheless, the causal effect is yet to be proven due to the lack of a appropriate animal model in performing the chronic studies which could simulate the slow PQ absorption under normal daily condition. Hence, this preliminary study aimed at analyzing the possible absorption of paraquat (PQ) in major organs flowing a 3-month PQ-treated diet. Four groups of rats were treated with normal diet and PQ-treated diet at different doses i.e. 30 mg/Kg, 60 mg/Kg and 100 mg/Kg, respectively. Upon the three months diet treatment, the major organs of the rats related to paraquat toxicity were harvested and subjected to conventional and immune-histopathological analysis. From the H&E histological analysis, non-significant differences among the among the major organs between the control and PQ-diet groups were anticipated. Nonetheless, from the immunohistochemical staining analysis, there might be a significant increase in the paraquat deposition or infiltration in the major organs, particularly the intestinal tissues wherein it is the frontline layers exposure to the PQ-diet. There might be a dose-dependen relationship between PQ doses and the immunohistochemical staining signal. In conclusion, the PQ-treat diet could be absorbed and detected in the living tissues following a PQ-treated diet. Effect of the toxic substances to the surrounding tissues could be investigated in future study.